Cytotoxic Activity of Stem of Pycnarrhena cauliflora through Apoptosis Induction on Human Breast Cancer Cell Line T47D - Masriani,; Rudiyansyah,; Muharini, Rini; Enawaty, Eny (UI Scholars Hub, 2019)
Cytotoxic activities of extracts of Pycnarrhena cauliflora leaves, stems and roots on some human cancer cells have been known. However, the cytotoxicity of stem of Pycnarrhena cauliflora on human breast cancer cell line T47D through an apoptosis induction has not been proven yet. This study was an effort in understanding the cytotoxic activity of stem of Pycnarrhena cauliflora through apoptosis induction. The crude ethanol extract was partitioned between n-hexane and dichloromethane at pH 3, 7 and 9, which was subsequently tested for their cytotoxic activity against human breast cancer cell line T47D by using 3-(4,5-dimethylthiazol-2-yl)- 2,5-diphenyltetrazolium bromide (MTT). Flow cytometric analysis with Annexin V-FLUOS/ propidium iodide (PI) double staining was used for apoptosis analysis. The dichloromethane fraction at pH 7 was considered the most potent with an IC50 value of 59.30 µg/mL and induced apoptosis on the T47D cell line. The result indicated the potential of dichloromethane fraction of the stem of P.cauliflora as a source of bioactiv